High-order redesign method for wind turbine blade optimization in model test considering aerodynamic similarity. (15th April 2020) - Chen, Zhe; He, Yanping; Zhao, Yongsheng; Meng, Long; He, Chong; Yang, He; Han, Zhaolong; Liu, Yadong
Abstract: The model test is important in the design and analysis of floating offshore wind turbines. However, the rotor thrust generated by the scaled model blades will be far less than the Froude-scaled value in the wave basin test, which has a significant effect on motion responses of floating offshore wind turbines. Thus, in order to improve the reliability of model tests, it is essential to simulate the rotor thrust accurately based on the aerodynamic similarity. In the present study, four parametric models were developed to define the geometry of model blades and they were integrated separately into the optimization model to reach the design criteria. Considering the weight control, the model blade defined by high-order design method was tested. It was demonstrated that the deviation between the experimental and numerical model blades under the rated condition was very small (only 3.16%). Under the same condition, the model blade with aerodynamic similarity could improve the rotor thrust by 106.33% compared with the Froude-scaled model blade. Simultaneously, high-order redesign method can significantly reduce the blade weight. Thus, the high-order redesign method is considered to be an effective way to eliminate the scale effect in the model tests of floating offshore wind turbines. Highlights: High-order redesign method to eliminate the scaling effect in the model test of floating offshore wind turbines. A new method to obtain model blades with the lightest weight considering aerodynamic similarity. Model test was conducted to test the rotor thrust of redesigned model blades. A good correlation with experimental data and numerical results.